2004
DOI: 10.1080/03078698.2004.9674309
|View full text |Cite
|
Sign up to set email alerts
|

Ringing recoveries confirm higher wader mortality in severe winters

Abstract: Periods of severe weather can result in significant mortality in bird populations. In Britain there is a system of voluntary, followed by official, bans on wildfowl hunting in coastal areas during periods of severely cold weather, in order to minimise disturbance to bird populations during these periods of energetic stress. The effectiveness of such hunting bans will be influenced by the spatial variation in severe weather and consequent mortality. Reports of dead ringed birds (recoveries) clearly show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…McCulloch & Clark (1992) found that Dunlin selected estuaries with higher minimum temperatures, as well as more westerly sites. Clark (2004) found increased mortality rates with severe freezing weather, but primarily on the east coast of the UK, particularly on the Wash. This increase in mortality was not nearly as strong on the west coast, even in smaller birds such as Dunlin.…”
Section: Severe Cold Weather Effectsmentioning
confidence: 88%
See 2 more Smart Citations
“…McCulloch & Clark (1992) found that Dunlin selected estuaries with higher minimum temperatures, as well as more westerly sites. Clark (2004) found increased mortality rates with severe freezing weather, but primarily on the east coast of the UK, particularly on the Wash. This increase in mortality was not nearly as strong on the west coast, even in smaller birds such as Dunlin.…”
Section: Severe Cold Weather Effectsmentioning
confidence: 88%
“…Wader mortality has been shown to substantially increase during periods of very cold weather (Dugan et al 1981, Davidson & Evans 1982, Davidson & Clark 1985, Clark 2004, 2009). The freezing temperatures affect the birds directly, by increasing metabolic stress (Dugan et al 1981, McCulloch & Clark 1992, Thompson & Hale 1993, Burton & Evans 1997, Warnock et al 1997, Kelly et al 2002 and indirectly, by affecting the behaviour of their prey (Goss-Custard 1969, Davidson 1981, as well as occasionally freezing the surface of the upper tidal mudflats (Thompson & Hale 1993).…”
Section: Severe Cold Weather Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weather may affect survival directly, for instance through increased metabolic requirements in cold weather (e.g. Clark , Pendlebury et al . ) or strong winds during migration (e.g.…”
mentioning
confidence: 99%
“…Birds may be killed or forced to move by severe weather (Dobinson & Richards 1964, Davidson & Evans 1982, Ridgill & Fox 1990, Mitchell et al 2000, Clark 2004), sometimes directly, but generally because they are unable to obtain sufficient food, particularly if energetic demands increase due to a fall in temperature or increase in wind speed. For example, short-term behavioural responses by animal prey to changing weather may change prey availability, making it more difficult for birds to find food.…”
mentioning
confidence: 99%